Deformation Behavior of Sandstones From the Seismogenic Groningen Gas Field: Role of Inelastic Versus Elastic Mechanisms. Issue 7 (17th July 2018) - Pijnenburg, R. P. J.; Verberne, B. A.; Hangx, S. J. T.; Spiers, C. J.
Abstract: Reduction of pore fluid pressure in sandstone oil, gas, or geothermal reservoirs causes elastic and possibly inelastic compaction of the reservoir, which may lead to surface subsidence and induced seismicity. While elastic compaction is well described using poroelasticity, inelastic and especially time‐dependent compactions are poorly constrained, and the underlying microphysical mechanisms are insufficiently understood. To help bridge this gap, we performed conventional triaxial compression experiments on samples recovered from the Slochteren sandstone reservoir in the seismogenic Groningen gas field in the Netherlands. Successive stages of active loading and stress relaxation were employed to study the partitioning between elastic versus time‐independent and time‐dependent inelastic deformations upon simulated pore pressure depletion. The results showed that inelastic strain developed from the onset of compression in all samples tested, revealing a nonlinear strain hardening trend to total axial strains of 0.4 to 1.3%, of which 0.1 to 0.8% were inelastic. Inelastic strains increased with increasing initial porosity (12–25%) and decreasing strain rate (10 −5  s −1 to 10 −9  s −1 ). Our results imply a porosity and rate‐dependent yield envelope that expands with increasing inelastic strain from the onset of compression. Microstructural evidence indicates that inelastic compaction was controlled by a combination of intergranular cracking, intergranular slip, and intragranular/transgranular cracking with intragranular/transgranular cracking increasing in importance with increasing porosity. The results imply that during pore pressure reduction in the Groningen field, the assumption of a poroelastic reservoir response leads to underestimation of the change in the effective horizontal stress and overestimation of the energy available for seismicity. Key Points: Triaxial tests on reservoir sandstone simulating gas depletion show inelastic strains (30–55% of total) Inelastic strain is porosity and rate dependent and develops from the onset of deformation, implying an expanding, porosity‐ and rate‐sensitive yield envelope This behavior should be incorporated in geomechanical modeling of reservoir depletion and induced seismicity